Mitigating operational risks in critical infrastructure through integrated ERP-BPMS: a multi-case study - Chernenko, Yuri; Bedrii, Dmytro; Haidaienko, Oksana; Meliksetov, Oleh (Technology audit and production reserves, 2025)
Operational risks in critical infrastructure sectors, from housing services and specialized construction to water technology and energy utilities, have significant socioeconomic implications. This study investigates how an integrated enterprise resource planning-business process management system (ERP-BPMS) supported by a dedicated information administrator (IA) can systematically mitigate these risks. Using a quasi-experimental, multi-case design, four anonymized organizations contributed baseline data (3–9 months) and post-implementation data (6–8 months). Six indicators were tracked: integral qualification score (IQS), cost prediction accuracy (CPA), system stability index (SSI), preventive maintenance ratio (PMR), sourcing score, and information utilization rate (IUR). Results reveal that IQS increased substantially in all cases (e. g., from 9.5 to 42.1), while CPA values commonly exceeded 0.85. Preventive maintenance ratios increased by 15–20 percentage points, indicating a notable shift from reactive to proactive strategies. In the energy utility case, the SSI improved from 1.04 to 1.31, showing enhanced service reliability. The IA’s oversight proved instrumental in ensuring consistent data governance, standardizing metrics, and streamlining cross-departmental coordination. These improvements translated into measurable resource savings that significantly outweighed the costs of maintaining the IA role. Cross-case analysis suggests that a staged implementation, beginning with pilot phases for core modules, can reveal data inconsistencies early and inform tailored training programs. Managers in sectors where cost accuracy and project timelines are critical may benefit substantially from such phased rollout. Collectively, these findings highlight that a unified ERP-BPMS platform reinforced by structured human governance can significantly bolster risk management in mission-critical contexts. This research contributes to both information systems and project management fields by offering a tested framework for enhancing resilience and operational stability in high-stakes environments.